2011
DOI: 10.1002/ijc.26072
|View full text |Cite
|
Sign up to set email alerts
|

Re‐expression of CEACAM1 long cytoplasmic domain isoform is associated with invasion and migration of colorectal cancer

Abstract: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is known to be downregulated at the transcriptional level in adenoma and carcinoma. Recent reports have shown that CEACAM1 is overexpressed at protein level in colorectal cancer and correlated with clinical stage. The reason why colorectal cancer cells re-expressed CEACAM1 remains unclear. The aim of our study was to clarify the implication of CEACAM1 re-expression in colorectal cancer. Immunohistochemical analyses were conducted with CEACAM1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 22 publications
15
76
0
Order By: Relevance
“…Stable CEACAM1-4S transfected LS174T cells had significantly reduced CEACAM1-4L mRNA and protein levels, which was confirmed by RT-PCR and western blot analyses as previously described 25. The CEACAM1 and CEACAM1-4L protein levels of these cells were significantly suppressed compared to those of the parental or vector-transfected cells (control) 25. CEACAM1-4S overexpressing cells reduced the number of colorectal hollow spheroids formed (p<0.01) (figure 3D).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Stable CEACAM1-4S transfected LS174T cells had significantly reduced CEACAM1-4L mRNA and protein levels, which was confirmed by RT-PCR and western blot analyses as previously described 25. The CEACAM1 and CEACAM1-4L protein levels of these cells were significantly suppressed compared to those of the parental or vector-transfected cells (control) 25. CEACAM1-4S overexpressing cells reduced the number of colorectal hollow spheroids formed (p<0.01) (figure 3D).…”
Section: Resultssupporting
confidence: 73%
“…In colorectal cancer, it is known that down-regulation of CEACAM1 occurs at the adenoma or early cancer stage,14 15 and CEACAM1 is re-expressed in advanced colorectal cancers 23 24. Recently, we showed that re-expressed CEACAM1, especially with long cytoplasmic domain dominance, in advanced colorectal carcinoma is associated with tumour metastasis and shorter survival 25. In the present study, we demonstrate that CEACAM1 isoform balance with long cytoplasmic domain dominance plays an important role in hollow spheroid formation in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that CEACAM1 actively contributed to tumor progression [25]. The reason for this discrepancy warrants further investigation but could be that CEACAM1 may have different roles in different cancers as discussed above [26, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…The CEACAM1 reactivity might be associated with metastatic spread, e.g., down-regulated in the early stage of the cancer and re-expressed in metastatic colon cancer [36]. The density of CEACAM1 expression was stronger at the invasion front of colorectal cancer in patients [37]. CEACAM1-L dominance might be an independent risk factor for lymph node metastasis, hematogenous metastasis, or short survival, and an important limiting factor for the invasion and migration of cancer cells.…”
Section: Roles Of Ceacam1 Apoptosismentioning
confidence: 99%